Strategic adaptation cross-cultural differences in company responses to an economic crisis - Sternad, Dietmar (SpringerWienNewYork, 2011)
This book explores the processes that are at work when companies adapt to environmental change, from strategic issue diagnosis and decision-making processes to specific strategic action that is taken in response to economic downturn.